Laju Infiltrasi Beberapa Jenis Tumbuhan Herba Di Matang Wildlife Centre, Sarawak - Karyati, Karyati; Ipor, Isa B.; Sapawi, Noorhana Mohd (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2014)
The existence of herbaceous was importance in order to the ability in soil and water conservation. A survey of soil infiltration rate at various land that dominated by herbaceous plants was conducted at Matang Wildlife Centre, Sarawak, East Malaysia. The highest infiltration rate (2.45 cm/minute) was observed at herb land which dominated by Mikania micrantha Kunth. The land that dominated by Fimbristylis glubolosa Vahl showed the lowest infiltration rate (0,06 cm/minute). According to growth types, the vegetation of herbaceous that categorized as boadleaf reached the highest infiltration rate (2.00 cm/minute), followed by fern (0.68 cm/minute) and grass (0.59 cm/minute). The infiltration rate of mixed dipterocarps forest which is situated near the study site was 2.56 cm/minute. Information about the infiltration rate of herbaceous plants is useful for soil and water conservation, biodiversity, and forest management and conservation.Keywords: Infiltration rate, herbaceous, cover crops, and Sarawak.